; обозначение : sqrt(2x+y²) ⇔√2x+y² !===============================((2x+y²) ^ (-1/2)) ' +(1/cosx)*(cosx) ' = 0;-1/2*(2x+y²)^(-3/2)*(2x+y²)' -tqx=0 ;-1/2*(2x+y²*)^(-3/2)*(2+2y*y') -tqx=0;-1/(2x+y2)^(3/2)*(1+y*y') -tqx=0 ;(1+y*y')/(2x+y²)^3/2 +tqx=0 ;1+y*y' = -tqx*(2x+y²)^3/2;y*y '= -tqx*(2x+y²)^3/2 -1;y ' = -1/y*(tqx*(2x+y²)^3/2 -1) .====================================1/√2x+y² = -Ln(cosx) ; √2x+y² = -1/Ln(cosx); [ Ln(cosx) <Ln1=0 ] ;2x+y² = 1/Ln²(cosx) ;y²= 1/Ln²(cosx) -2x ;y = (+/-√(1/Ln²(cosx) -2x ) .